Skazka myshka i rjabchik - Andrey Filchenko; Nadia Fedotova; Sergej Kovylin; M.S.Karelin; G.K.Verner; N.P.Maksimova (Andrey Filchenko, 2014)
Southern Selkup, . river, text recorded in ., by researcher ., from speaker . born in . in Ozernoe village, speaker bi-lingual Selkup-Russian, education - . Archived: Tomsk TSPU Field Archive. Volume C-. pp. Manuscript scanned by J. in 2012; annotated and translated by ., in 2013. Previously .published. Автор текста (рассказчик): . Родился прим. в . г. в . Образование среднее. Жил в . Автор записи (кем записано): .: Записано в . г. в п. ., Томская область. Хранится: Архив ЯНС ТГПУ: Том C-., стр. . Манускрипт оцифрован каф. ЯНС: - сканирование: ., 2012 - набор, глосиирование и перевод: ., 2013 Ранее . публиковался. Comprehensive Documentation & Analysis of two Endangered Siberian Languages: legacy data and last speakers of Eastern Khanty and Southern Selkup Southern Selkup legacy text data. Speaker: Karelin Matvej Semenovich, born 1916, in Ust-Ozernoe village. Recorded by G.K.Verner, in 1962, in Ust-Ozernoe village. Manuscript scanned: Sergej Kovylin in 2012. Transcribed and translated: Sergej Kovylin, Nadia Fedotova, Natalija Maksimova, Andrey Filchenko. Archived: Tomsk archive - V: C-5, pp.783-790. Южно селькупский текст. Автор текста (рассказчик): Карелин Матвей Семенович; 1916 г.р.; Окончил 7 классов на русском языке, обучался и родному языку. Русский язык знает хорошо. Работает председателем сель. совета 5 лет. Работал раньше инструктором раисполкома. Окончил один курс пед. училища в Колпашево. В настоящее время проживает в Усть-Озерном. Автор записи: Генрих Каспарович Вернер; Когда Записано: 1962; Где записано: Усть-Озерное; Манускрипт оцифрован каф. ЯНС: Ковылин С.В. 2012. Набор, глоссирование и перевод: Сергей Ковылин, Надья Федотова, Наталья Максимова, Андрей Фильченко. Архив КЯНС ТГПУ, том С-5, сс.783-790. Southern Selkup Born in 1916. Lived in Ust-Ozernoe village. Education - middle + professional training. birth year approximate